# L’Hopital’s Rule

Adrian Down 16779577 July 20, 2005

1

Motivation

Comes as a direct consequence of the Mean Value theorem. Useful for computing limits of the form f (x) where f (x), g(x) → 0. Connected to g(x)
(x) limx→a f (x) . Assume f (a) = g(a) = 0, and you want to compute limx→a f (x) . g g(x) Use the mean value theorem to try to approximate the function. As x approaches a, f (x) should be approximately f (a) + f (y)(x − a). Using the mean value theorem, we know such a y exists, so f (x) = f (a) + f (y)(x − a) for some a < y < x. Likewise, g(x) = g(a) + g (z)(x − a) for some a < z < x. So

f (y)(x − a) f (y) f (x) f (x) = = ≈ g(x) g (z)(x − a) g (z) f (y) since y and z approach x as x approaches a. Keep this idea in mind for the proof.

2

Proof

Theorem (generalized mean value theorem): let f, g be continuous on [a, b], and diﬀerentiable on (a, b). Then ∃x ∈ (a, b) such that f (x) · (g(b) − g(a)) = g (x)(f (b) − f (a)). Note: another way to think about this is that if g (x) = 0, then f (x) f (b) − f (a) = g (x) g(b) − g(a) 1

This is exactly the thing that we want to take the limit of from our heuristic argument above. Will tell us that we can take y and z to be the same. Proof: same as the mean value theorem. Make a diﬀerence function, h(x) = f (x)(g(b) − g(a)) − g(x)(f (b) − f (a)). Note that it is diﬀerentiable on (a, b) and continuous on [a, b]. Do computation to get that h(a) = h(b). By Rolle’s theorem, ∃x ∈ (a, b) such that h (x) = 0. Note that the f (a), g(a), etc. terms in h are constants, so h (x) = f (x)(g(b) − g(a)) − g (x)(f (b) − f (a)) h (x) = 0 → f (x)(g(b) − g(a)) = g (x)(f (b) − f (a)) Note that this theorem reduces to the mean value theorem by taking g(x) = x. Theorem: let f, g be diﬀerentiable functions (on an open interval I con(x) taining some point a) such that g is continuous on I and limx→a f (x) exg ists is ﬁnite, and equals L ∈ R, if limx→a f (x) = limx→a g(x) = 0, then limx→a f (x) = L. g(x) Note: we need the fact that g (x) = 0 in some area close to a. Proof: let > 0. Can take g = 0 on I by shrinking I if necessary → g is strictly increasing or strictly decreasing → g is invertible on I → g (x) = 0 for at most 1 x ∈ I. Shrink I so that g = 0 on I. The lesson is that if there could be problems on our interval, we can shrink it to a safe area since we’re taking the limit. Let K ∈ R such that L < K < L+ . Want to get the quotient between L (x) (x) and K. limx→a f (x) = L → ∃α > 0 such that a < x < α → f (x) < K (taking g g = K −L in the deﬁnition of the limit). If a < x < y < α → ∃z ∈ (x, y) such (z) that f (x)−f (y) = f (z) by the generalized mean value theorem → f (x)−f (y) < K g(x)−g(y) g g(x)−g(y) because a < z < α. Now take the limit as x approaches a with y ﬁxed. Then
x→a

lim+

f (x) − f (y) ≤K g(x) − g(y)

but as x approaches a, lim f (x) = lim g(x) = 0, so f (y) ≤ K. g(y) Aside: limx→a+ f (x) = L → ∀ > 0, ∃δ > 0 such that a < x < a + δ → |f (x) − L| < . So f (y) ≤ K < L + is true ∀y ∈ (a, α). Halfway to making our limit. g(y) Similarly, ∃β such that β < y < a → f (y) > L − by taking L − < K < L g(y) and using the same argument as before. 2

Take δ = min{α − a, a − β}, so if 0 < |x − a| < δ →
f (x) g(x)

f (x) g(x)

< L+

and

> L − , so − L| < Key idea is just applying the mean value theorem to go from the ratio of quantities to a ratio of derivatives, and then using the fact that limx→a f (x) = limx→a g(x) = 0. Notes: 1) If limx→a f (x) = limx→a g(x) = ∞, then the theorem still holds 2) Can also consider limx→∞ or limx→−∞ or limx→a+ or limx→a− . 3) 0 is called an indeterminate form, as is ∞ . Others are 0·∞, 00 . L’Hopital’s 0 ∞ rule applies to all of these. 4)L’Hopital’s rule is NOT applicable to ∞ . 0

| f (x) g(x)

3

Examples

sin 1) limx→0 cosxx−1 = limx→0 − 2x x = limx→0 − cos x = − 1 . 2 2 2 2 2) limx→∞ xx = limx→∞ 2x = limx→∞ e2 = 0. x e ex

3) limx→0+ x · ln x = limx→0+

ln x
1 x

= limx→0+

4) limx→0 xx = limx→0+ ex ln x . Because ex is continuous, take the limit of the exponent separately. From the last example, it is 0. Thus the given limit is e0 = 1. 1 1 1 1 x 5) limx→∞ x x = limx→∞ e x ln x . limx→∞ x ln x = limx→∞ 1 = 0
1 1 6) limx→∞ (1+ x )x = limx→∞ ex ln(1+ x ) . limx→∞ x·ln(1+ x ) = limx→∞
1 −1 1 ) 1 ( 1+ x x2 −1 ( 2 x ) 1 x

1 x −1 x2

= limx→0+ −x = 0

1 ln(1+ x )

=

limx→∞
−1 2

1 7) limx→0 ( ex1 − x ) = limx→0 −1

x−ex +1 x(ex −1)

= limx→0

1−ex xex +ex +1

= limx→0

−ex xex +2ex

=

Useful for functions that get simpler or stay the same when diﬀerentiated. Useful for polynomials, trig functions, and exponentials. Note: limx→a f (x) = +∞ → ∀M, ∃δ such that 0 < |x−a| < δ → |f (x)| > M.

3